2010
DOI: 10.1111/j.1469-8137.2010.03324.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of ectomycorrhizal mycelium peaks during canopy closure in Norway spruce forests

Abstract: Summary• Here, species composition and biomass production of actively growing ectomycorrhizal (EM) mycelia were studied over the rotation period of managed Norway spruce (Picea abies) stands in south-western Sweden.• The EM mycelia were collected using ingrowth mesh bags incubated in the forest soil during one growing season. Fungal biomass was estimated by ergosterol analysis and the EM species were identified by 454 sequencing of internal transcribed spacer (ITS) amplicons. Nutrient availability and the fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
144
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(167 citation statements)
references
References 49 publications
15
144
3
1
Order By: Relevance
“…Wallander et al (2010) found on average 70% ECM fungi in similar mesh bags without OM amendment in the same experimental site. However, the addition of compost in the present study resulted in a higher proportion of saprophytic fungi, and ECM fungi constituted 30-43% of the fungal abundance.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Wallander et al (2010) found on average 70% ECM fungi in similar mesh bags without OM amendment in the same experimental site. However, the addition of compost in the present study resulted in a higher proportion of saprophytic fungi, and ECM fungi constituted 30-43% of the fungal abundance.…”
Section: Discussionmentioning
confidence: 63%
“…Fungal colonization and community composition of the mesh bags Colonization of sand-filled mesh bags is usually dominated by ECM fungi, although a lesser amount of saprotrophic fungi is also present (Wallander et al 2001(Wallander et al , 2010. Wallander et al (2010) found on average 70% ECM fungi in similar mesh bags without OM amendment in the same experimental site.…”
Section: Discussionmentioning
confidence: 92%
“…This occurs between 25 to 40 years of age in P. abies forests in central-southern Sweden (Schmalholz and Hylander 2009). The production of EMM seems to peak around the time when tree growth is highest (Wallander et al 2010;Kalliokoski et al 2010). …”
Section: Seasonal Effects and Forest Agingmentioning
confidence: 99%
“…Hyphal in-growth cores or bags are commonly used (Wallander et al, 2001). These hyphae traps are usually filled with an inert substrate, such as sand, that minimizes colonization by saprotrophic fungi (Korkama et al, 2007;Lindahl et al, 2007;Wallander et al, 2010). In some cases, additional nutrient sources are added to ensure sufficient hyphal colonization or to evaluate the impact of limiting nutrients on EMF biomass production (Hagerberg and Wallander, 2002;Hagerberg et al, 2003;Hedh et al, 2008;Potila et al, 2009;Berner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%